Interstitial Lung Disease in Rheumatoid Arthritis: A Practical Review - Laria, Antonella; Lurati, Alfredo Maria; Zizzo, Gaetano; Zaccara, Eleonora; Mazzocchi, Daniela; Re, Katia Angela; Marrazza, Mariagrazia; Faggioli, Paola; Mazzone, Antonino (Frontiers in Medicine, 2022)
Rheumatoid arthritis (RA) is a systemic inflammatory disease, which primarily causes symmetric polyarthritis. An extrarticolar involvement is common, and the commonly involved organ is lungs. Although cardiac disease is responsible for most RA-related deaths, pulmonary disease is also a major contributor, accounting for ~10–20% of all mortality. Pulmonary disease is a common (60–80% of patients with RA) extra-articular complication of RA. Optimal screening, diagnostic, and treatment strategies of pulmonary disease remain uncertain, which have been the focus of an ongoing investigation. Clinicians should regularly assess patients with RA for the signs and symptoms of pulmonary disease and, reciprocally, consider RA and other connective tissue diseases when evaluating a patient with pulmonary disease of an unknown etiology. RA directly affects all anatomic compartments of the thorax, including the lung parenchyma, large and small airways, pleura, and less commonly vessels. In addition, pulmonary infection and drug-induced lung disease associated with immunosuppressive agents used for the treatment of RA may occur.